The Direct Medical Costs of Late Presentation (<350/mm3) of HIV Infection over a 15-Year Period - Hartmut B. Krentz; M. John Gill (AIDS Research and Treatment, 2012)
We describe the immediate- and longer-term direct medical costs of care for individuals diagnosed with HIV at CD4 counts <350/mm3 (“late presenters”). We collected and stratified by initial CD4 count all inpatient, outpatient, and drug costs for all newly diagnosed patients accessing HIV care within Southern Alberta from 1/1/1995 to 1/1/2010. 59% of new patients were late presenters. We found significantly higher costs for late presenters, especially inpatient costs, during the first year after accessing care. Direct medical costs remained almost twice as high for late presenters in subsequent years compared to patients presenting with CD4 counts >350/mm3 despite significantly their improved CD4 counts. The sustained high cost for late presenters has implications for recent recommendations for wider routine HIV testing and the earlier initiation of cART. Earlier diagnosis and treatment, while increasing the immediate expenditures within a population, may produce both direct and indirect cost savings in the longer term.